HIV-AIDS AND ISLAM’ IN INDONESIA; POWER NARRATIVES AND RESISTANCE - Syamsu Madyan (Universitas Islam Malang, 2019)
This paper can be identified as an AIDS anti-stigma related project, which orients its query to the particular problem of social stigma based on religion in Indonesia. It analyze how Islamic authorities and leadership in Indonesia has the power in the construction of AIDS realities as the reproduction of AIDS discourses in Indonesia generates the stigma towards Muslims living with the infection. This paper will be demonstrating the scenario of power, exclusion and resistance within the context of that stigma.Keywords: AIDS, religion, resistence